The blue layer - Atkinson, Kathie (Nelson South Melbourne, Vic., 1994)
The Blue Layer by Kathie Atkinson delves into the mysteries of the deep ocean, exploring the interactions between marine life and the unseen forces that shape their environment. The narrative intertwines scientific discoveries with personal reflection, revealing the intricate connections between humanity and the underwater world.